Performance Analysis of the Archimedes Double Screw Turbine as a Micro Hydro Power Plant with Varying Flow Rate - Irwansyah Syam (Jurnal Inotera, 2023)
Samadua is an area in South Aceh Regency which has a lot of water energy potential to be used as energy to drive water turbines. The potential for water energy, it is necessary to develop renewable energy power technology, namely micro hydro power plants that can be utilized by the community. The type of water turbine that is suitable for application in the area that have water potential with low head and discharge is the Archimedes Double Screw Turbine. The Archimedes double screw turbine is a type of turbine that capable of operating with a low head of 1-15 m in river flows and irrigation and has the advantage of being environmentally friendly. The aim of this research is to design and manufacture an Archimedes Double Screw turbine that is appropriate and in accordance with the real conditions in the stream of Samadua river, -South Aceh, then analyze the influence and determine the torque ratio on the performance of the Archimedes Double Screw Turbine by measuring rotation speed, torque, power and efficiency based on variations in river flow rate. The Archimedes Double Screw turbine is made from 201 stainless steel which has dimensions of N = 2 blades (= 260 mm, = 140 mm) with a pitch of 2Ro, turbine length (L = 2 m), head = 1 m, angle θ = 300. The variables measured and observed are turbine rotation, torque, and flow rate. Tests were carried out on 3 variations of flow discharge, namely 0.02 m3/s, 0.009 m3/s, and 0.003 m3/s. The test results showed that the highest turbine rotation and power occurred at a flow rate of 0.02 m3/s of 292.10 rpm and 122.20 watts and the maximum turbine efficiency was 62%. Thus, the turbine with maximum power is obtained when the flow rate is 0.02 m3/s, while the turbine with maximum efficiency is obtained when the flow rate is 0.02 m3/s. For the numerical simulation results, the optimum pressure distribution value is 4.873 kPa and the minimum is 0.1536 kPa, so the comparison of the experimental results with the numerical simulation is that the numerical simulation optimum torque value is 2.50 N/m and the experimental optimum torque value is 2.00 N /m.